Research on the Degree of Concern of Romanian Entrepreneurs in the Field of Cyber Security - Petronela Cristina SIMION; Mirona Ana Maria POPESCU; Andrei MITROFAN; Iustina Cristina COSTEA-MARCU (Communications of International Proceedings, 2022)
The issue of cybersecurity has become a very important issue in the modern world. The rapid advancement of technology has made it easier to access sensitive information, which is why companies are increasingly concerned about cyber security threats. With the rise of cyber threats and hacking, cyber security is becoming a matter of urgency and security for all organizations. Combating cyber threats is a complex challenge and small business as well as start-ups need to pay more attention to the risks they face as their security systems become less developed. The authors present the main concepts related to cybersecurity and underline how this may occure in the SMEs environment. A survey was developed and completed by Romanian SMEs to determine the main causes that lead to the emergence of cyber security risks as many of them do not have a person/department dedicated to deal with this type of issues. Statistics concerning malware campaigns made in Romania to raise awareness and the most common types of attacks were presented as a base for further studies and an overview of the current context.
Keywords: Cybersecurity; Romanian SMEs; cyber attacks; cybersecurity risks